2018
DOI: 10.12697/akut.2017.23.04
|View full text |Cite
|
Sign up to set email alerts
|

The half-marathon participants, who are they and what motivates them for training and competition?

Abstract: The purposes of the present study was to investigate the motives for training and competing among participants in a half-marathon race. A descriptive quantitative research design was developed using a questionnaire to examine the half-marathon runners' interest in running and competition. The total number of participants presented in this study were 862, 331 female and 531 male with a mean age 41.8±10.4 years. The major reasons for the participants to regularly practice running were because of its importance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Our data also suggests that this set of runners presents higher score in autonomous forms of behavior regulation (intrinsic, integrated and identified). Previous research about running motives suggests physical and mental health as the main motives for engaging in running [ 34 37 ]. Additionally, these findings are similar with those found with female ultra-runners, proposing general health orientation, self-esteem and psychological coping as the strongest motivational factors [ 35 ], with half, full and ultra-marathoners, identifying health orientation, personal goal achievement and self-esteem [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data also suggests that this set of runners presents higher score in autonomous forms of behavior regulation (intrinsic, integrated and identified). Previous research about running motives suggests physical and mental health as the main motives for engaging in running [ 34 37 ]. Additionally, these findings are similar with those found with female ultra-runners, proposing general health orientation, self-esteem and psychological coping as the strongest motivational factors [ 35 ], with half, full and ultra-marathoners, identifying health orientation, personal goal achievement and self-esteem [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen cross-sectional studies described or compared motives between groups of runners. Among the highest-ranked motives reported were physical health (Krouse et al, 2011), psychological motives (Tjelta et al, 2017), health orientation (Malchrowicz-Mośko et al, 2020), and personal achievement (Doppelmayr and Molkenthin, 2004). Less frequent or lowerranked motives were competition (Leedy, 2000), social motives, such as affiliation or social comparison (Malchrowicz-Moko et al, 2018), and also having fun (Tjelta et al, 2017).…”
Section: Antecedents Of Recreational Runningmentioning
confidence: 99%
“…Studies comparing motives between different groups found that age (Ogles and Masters, 2000), gender (Tjelta et al, 2017), experience in running (Masters and Ogles, 1995), training profile (Ogles et al, 1995), and type of event (Doppelmayr and Molkenthin, 2004) were associated with different motives. Younger runners were more motivated by personal goal achievement and competition (Pereira et al, 2021).…”
Section: Antecedents Of Recreational Runningmentioning
confidence: 99%
See 1 more Smart Citation
“…Every runner has their own motives to run and these differ depending on gender, age, experience and running distance (Bell & Stephenson, 2014;Fosberg, 2015;Hanson, Madaras, Dicke, & Buckworth, 2015;Krouse et al, 2011;Kuru, 2016;Masters, Ogles, & Jolton, 1993;Ogles & Masters, 2003;Ogles, Masters, & Richardson, 1995;Rohm, Milner, & McDonald, 2006;Shipway & Holloway, 2013;Stragier, Vanden Abeele, & De Marez, 2018;Tjelta, Kvåle, & Shalfawi, 2018). The feedback content that each individual prefers differs depending on the motive(s) to run (Breedveld, Scheerder, & Borgers, 2015;Deelen, Ettema, & Kamphuis, 2018;Janssen et al, 2017;Stragier et al, 2018;Vos, Janssen, Goudsmit, Lauwerijssen, & Brombacher, 2016).…”
Section: Motives To Run and Differences In Preferred Feedback Contentmentioning
confidence: 99%